2012
DOI: 10.1590/s0102-695x2011005000173
|View full text |Cite
|
Sign up to set email alerts
|

Phythochemical screening and antimicrobial activity phythochemical of essential oil from Lippia gracillis

Abstract: Abstract:The chemical composition of the essential oil obtained from the fresh and dried leaves of Lippia gracillis Schauer, Verbenaceae, was analyzed by gas chromatography and gas chromatography/mass spectrometry (GC⁄MS). The yield of essential oil extracted from the dried leaves was significantly higher (p<0.05) when compared to the fresh leaves. Seventeen components were identified. The monoterpenes and sesquiterpene hydrocarbons with 96.26% (w/w) of the total oil obtained of fresh leaves and 86.99% (w/w) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
(41 reference statements)
0
7
0
3
Order By: Relevance
“…However, studies by Bitu et al (2012) showed that there are significant differences when comparing the chemical composition and antimicrobial activity of essential oils from fresh and dried rosemary leaves, where the biological activity can be modified by the leaf drying process.…”
Section: Data Relating To Medicinal Plants Soldmentioning
confidence: 99%
“…However, studies by Bitu et al (2012) showed that there are significant differences when comparing the chemical composition and antimicrobial activity of essential oils from fresh and dried rosemary leaves, where the biological activity can be modified by the leaf drying process.…”
Section: Data Relating To Medicinal Plants Soldmentioning
confidence: 99%
“…Results of MIC was considered positive for those wells with blue coloring indicating absence of visible microbial growth, and negative for those wells in red due the presence of viable cells 13,14 .…”
Section: Determinationmentioning
confidence: 99%
“…Several studies to identify antimicrobial activity have been conducted with plants that have high percentages of β-caryophyllene in their composition, presenting positive results for these extracts against several pathogens: Thymus kotschyanus [18], Spiranthera odoratissima [19], Lantana sp. [20], Vernonia remotiflorae V. brasiliana [21], Syzygium cumini [22], and Lippia gracillis [23], among others.
Fig. 1Chemical structure of β-caryophyllene (4,11,11-trimethyl-8-methylene-bicyclo[7.2.0]undec-4-ene)
…”
Section: Introductionmentioning
confidence: 99%